Corruption effect on foreign direct investments in European Union countries - Navickas, Valentinas; Navickas, Mykolas; Kordoš, Marcel (Business: Theory and Practice, 2016)
The authors of the article analyze the effect of corruption on foreign direct investments in most corrupt European Union countries. Corruption in the context of the analysis is understood as an act where government officials enter into an agreement with a foreign investors against the interest of society. It takes place when illegal payments for government are made. Such payments acts as an additional tax on investments in foreign country, thus decreasing attractiveness of investment for foreign investors. There are various types of corruption, but most common classification include grand corruption, petty corruption and public sector corruption. However, this article focuses on the effect of grand corruption, because it directly affects FDI inflows in particular country. Results of the research made by the authors shows that corruption has adverse effect on FDI inflows, however particular corrupt actions may postively effect FDI inflows. In order to determine corruption effect on FDI in corrupt EU countries statistical analysis of 2000–2014 period has been implemented and conceptual model of effect on FDI created.